2005
DOI: 10.1080/13607860512331339090
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural symptoms of dementia in residential settings: A selective review of non-pharmacological interventions

Abstract: For people with dementia living in residential settings, behaviours such as aggression, screaming, restlessness, agitation and wandering are a frequent reason for referral to specialist mental health services for older people. Psychosocial models of dementia have grown in prominence and non-pharmacological interventions have been recommended in professional and government policy statements, either as a first line of treatment or alongside medication. Studies of their effectiveness have been criticised for bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
43
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 62 publications
0
43
0
2
Order By: Relevance
“…Innovative and effective nonpharmacological treatments for depression and challenging behaviors have become more widespread in recent years (Camp, Cohen-Mansfield, & Capezuti, 2002;Landreville et al, 2006;Turner, 2005). In a comprehensive review, Opie, Doyle, and O'Connor (2002) concluded that there is evidence to support the efficacy of non-pharmacological interventions for behavioural disorders in dementia.…”
Section: Introductionmentioning
confidence: 98%
“…Innovative and effective nonpharmacological treatments for depression and challenging behaviors have become more widespread in recent years (Camp, Cohen-Mansfield, & Capezuti, 2002;Landreville et al, 2006;Turner, 2005). In a comprehensive review, Opie, Doyle, and O'Connor (2002) concluded that there is evidence to support the efficacy of non-pharmacological interventions for behavioural disorders in dementia.…”
Section: Introductionmentioning
confidence: 98%
“…In the light of such concerns, Howard and colleagues ' (2001) guidelines suggest that non-pharmacological interventions should be used prior to the use of pharmacological treatments. Turner (2005) argues that effective non-pharmacological interventions, for individuals displaying challenging behaviour, should be based on a multifaceted approach to assessment. She suggests that one employs applied behaviour analytic techniques within clinical formulations, such as conducting a functional analysis of people's challenging behaviour.…”
mentioning
confidence: 99%
“…Tijdschrift voor Gerontologie en Geriatrie, 2005(2005 In het gunstigste geval worden dergelijke interventies ondersteund met onderzoek en advies door een psycholoog, en kan een gerontopsychiater worden geconsulteerd. Over de effectiviteit van psychosociale interventies bij individuele patie¨nten wordt opmerkelijk weinig in de wetenschappelijke literatuur gerapporteerd.…”
unclassified